RNAi-mediated rheostat for dynamic control of AAV-delivered transgenes - Megha Subramanian; James McIninch; Ivan Zlatev; Mark K. Schlegel; Charalambos Kaittanis; Tuyen Nguyen; Saket Agarwal; Timothy Racie; Martha Arbaiza Alvarado; Kelly Wassarman; Thomas S. Collins; Tyler Chickering; et al. (Nature Communications, 2023)
Here the authors propose an RNA interference-based switch for dynamic control of AAV transgene expression. In this approach, transgene expression may be silenced by RNAi and subsequently recovered using REVERSIR oligonucleotides.